Strategi Industrialisasi: Hubungan Dengan Sektor Lain - Mahardhika Harilinawan; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The industrial sector contributes greatly to national economic development through increasing added value, creating jobs and providing foreign exchange. The government and investors need to know the sectors that play an important role in the economy. An industrialization strategy is needed to overcome challenges in industrial development and achieve Indonesia's vision as a sovereign, advanced, just and prosperous country. Structural transformations are important in economic development, including changes from agriculture to non-agriculture and from industry to services. Industrialization is considered a path to advanced economic development. The government in Indonesia is trying to advance industry, especially in the agricultural sector which has great potential for economic development.